1974
DOI: 10.1111/j.1744-6570.1974.tb01173.x
|View full text |Cite
|
Sign up to set email alerts
|

Realistic Work Sample Tests: A Review

Abstract: INFORMATION with the highest validity seems to have a pobnt-topoint correspondence with the criterion. For instance, in a review article of the scorable application blank, Asher (1972) concluded that biographical information showed substantially higher predictive validity when job proficiency was the criterion, than other predictors including tests of intelligence, personality, interest, perception, motor skill, and mechanical ability.The generalization seemed t o be that factual and verifiable historical info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
93
0
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(97 citation statements)
references
References 61 publications
2
93
0
2
Order By: Relevance
“…Meta-analytic reviews have indicated that work samples have high criterion-related validity for predicting job performance (Roth, Bobko, & McFarland, 2005;Schmidt & Hunter, 1998). Furthermore, as work samples have a higher degree of fidelity to tasks performed on the job than traditional individual differences predictors (Asher & Sciarrino, 1974), they are generally associated with more favorable applicant reactions (e.g., Hausknecht, Day, & Thomas, 2004;Macan, Avedon, Paese, & Smith, 1994).…”
mentioning
confidence: 99%
“…Meta-analytic reviews have indicated that work samples have high criterion-related validity for predicting job performance (Roth, Bobko, & McFarland, 2005;Schmidt & Hunter, 1998). Furthermore, as work samples have a higher degree of fidelity to tasks performed on the job than traditional individual differences predictors (Asher & Sciarrino, 1974), they are generally associated with more favorable applicant reactions (e.g., Hausknecht, Day, & Thomas, 2004;Macan, Avedon, Paese, & Smith, 1994).…”
mentioning
confidence: 99%
“…Based on these results, Roth et al (2005) emphasized that work sample validity could be noticeably lower than previously thought and therefore some organizations may be overestimating the validity properties of work samples. Despite the lower validity estimates that were obtained in more recent studies, which have overcome important limitations related with conceptual and methodological problems (Asher & Sciarrino, 1974) on the one hand, and the limited scope on the other, in general, the directionality of the results of the studies converge on an indication that work sample tests are valid predictors of job performance.…”
Section: Validity Of Work Sample Testsmentioning
confidence: 98%
“…In my first week of graduate school, I found myself assigned to write the inaugural paper of my career on the subject of work samples. Though I knew almost nothing about personnel selection at that time, my research led me to Asher and Sciarrino (1974), an article that immediately had a strong intuitive appeal and still remains a foundational element in my philosophy of personnel selection. In this article, the authors introduce the concept of "point to point correspondence," a concept suggesting that prediction is enhanced when predictors are designed to be miniature replicas of the criterion space.…”
Section: Forewordmentioning
confidence: 99%